2019
DOI: 10.1021/acsabm.8b00816
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Study of Cerium Oxide Nanoparticles: New Insights into Antiamyloidogenic Activity

Abstract: There seems to be general agreement that oxidative stress is involved in many pathological conditions including Parkinson’s, Alzheimer’s, and other neurodegenerative diseases, and overall aging. Cerium oxide nanoparticles, also known as nanoceria (CeO2–NPs), have shown promise as catalytic antioxidants, based on their ability to switch between Ce3+ and Ce4+ valence states. In the present work we have synthesized and characterized CeO2–NPs, examined the effect of CeO2–NPs on amyloidogenesis of insulin, and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…The cancer cells became highly adaptive to intracellular oxidative stress and revealed the way how to rescue and survive [60,67]. Recently, it was shown that the nanoceria applied to the U87 MG cells locally increased the oxidative stress level in the perinuclear area without affection of the cell proliferation [68]. One can expect the same behavior in cells treated with SBA-1.…”
Section: The Cytotoxicity Of Sba-15 and Sba-15_n-ani_5-fu_β-cd Systemmentioning
confidence: 87%
“…The cancer cells became highly adaptive to intracellular oxidative stress and revealed the way how to rescue and survive [60,67]. Recently, it was shown that the nanoceria applied to the U87 MG cells locally increased the oxidative stress level in the perinuclear area without affection of the cell proliferation [68]. One can expect the same behavior in cells treated with SBA-1.…”
Section: The Cytotoxicity Of Sba-15 and Sba-15_n-ani_5-fu_β-cd Systemmentioning
confidence: 87%
“…The IC 50 (the concentration of CZs required to inhibit fibril formation by 50%) and DC 50 (the concentration of CZs required to disassemble preformed fibrils by 50%) values were determined from fitting the dose-dependent experimental data using the nonlinear least-squares analysis with the sigmoidal sigmoid 3/4 parameter equation as described recently 36,37 . www.nature.com/scientificreports/ Anti-amyloidogenic activity assessment: microscopy techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, these nanoparticles are incorporated with a fluorite crystalline lattice structure, resulting in a higher reactive surface area to scavenge free radicals. Owing to a lower redox potential (=1.52 v), CeO 2 nanoparticles can shift between Ce 3+ and Ce 4+ , depending upon the experimental conditions, a key feature for using CeO 2 nanoparticles as an antioxidant carrier (Siposova et al, 2019 ). Furthermore, the redox property of CeO 2 nanoparticles has been widely utilized against ROS-based tissue damage.…”
Section: Internal Stimuli-responsive Metallic Nanotherapeuticsmentioning
confidence: 99%